Software Development For Design Of AOQ/AOQL Attribute Sampling Plan For Manufacturing Industries - Raja Ghazilla, Raja Najihah (Universiti Sains Malaysia, 2004)
Nowadays, quality control plays an important role in every manufacturing environment. As an effort to maintain the quality of the manufactured product many type of quality control has been implemented. One of them is the well-known acceptance-sampling plan, which can be classified into two categories, which is attributes and variables. There are many way on how to derive a sampling plan. One of them is through the usage of sampling plan table that is ready to be used. Even though it is a quite popular in deriving a sampling plan, sometimes it is quite difficult to administer. It is also a time consuming method and sometimes are not able to give the exact results. As an answer for the above problem, a study has been done on developing software for acceptance sampling plan. The main criterion of this project is to develop an attribute acceptance-sampling plan on a basis of AOQ and AOQL parameters. This project presentation is only about the Double Sampling plan. The first step in this project is to study the principles and the theories of acceptance sampling plan particularly Double Sampling plan. It is very essential to gain all the information and to determine all the necessary data used to develop a sampling plan. The final step is to learn all the basic rules of C programming language. After having a solid knowledge about C programming language, then it would be easier apply all the relevant equations and formulas into programming codes.